2014
DOI: 10.9721/kjfst.2014.46.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Anti-mycobacterial Effects of the Extract of Humulus japonicus

Abstract: The present study aimed to evaluate the in vitro antimycobacterial effects of hop plant, Humulus japonicus. Methanol extract of H. japonicus (MeOH extract) showed strong direct bactericidal effects against Mycobacterium tuberculosis in vitro. Furthermore, the MeOH extract significantly inhibited M. tuberculosis growth in human macrophages. When five fractions obtained from MeOH extract were examined using the same methods, the hexane and ethyl acetate fractions showed bactericidal effects against M. tuberculos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The anti-inflammatory capability of HJ may contribute to its anti-microbial, anti-mycobacterial and anticancer effects (20,21,50,51). Although it was not verified in this study, previous studies have shown that HJ has an antioxidant activity in vitro (20,21,51).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory capability of HJ may contribute to its anti-microbial, anti-mycobacterial and anticancer effects (20,21,50,51). Although it was not verified in this study, previous studies have shown that HJ has an antioxidant activity in vitro (20,21,51).…”
Section: Discussionmentioning
confidence: 99%
“…H. japonicus has long been used in traditional medicine to cure skin diseases, pulmonary tuberculosis, and hypertension [ 50 ]. Other biological effects of H. japonicus include antimutagenic, antibacterial, antiatheroma, antioxidant, antitumor, antimycobacterial, and anti-inflammatory effects [ 50 , 51 , 52 , 53 , 54 ].…”
Section: Plant Extracts That Stimulate Adipocyte Browningmentioning
confidence: 99%
“…It has been demonstrated that the pollen of this plant is allergenic, and is considered as one of the major causes of pollen allergy ( 16 ). To date, HJ has been reported to exert anti-mutagenic ( 17 ), antimicrobial ( 18 ), antioxidant ( 18 , 19 ), anticancer ( 19 ), anti-mycobacterial ( 20 ), and anti-inflammatory ( 21 ) effects. From the results of previous studies, we speculated that the antioxidant and anti-inflammatory effects of HJ may also contribute to the anti-atherosclerotic effect of HJ.…”
Section: Introductionmentioning
confidence: 99%